You play the girl: on Playboy bunnies, Stepford wives, train wrecks, and other mixed messages - Chocano, Carina (Houghton Mifflin Harcourt, 2017)
"Who is "the girl"? Look to movies, TV shows, magazines, and ads and the message is both clear and not: she is a sexed-up sidekick, a princess waiting to be saved, a morally infallible angel with no opinions of her own. She's whatever the hero needs her to be in order to become himself. She's an abstraction, an ideal, a standard, a mercurial phantom. In You Play the Girl, Chocano blends formative personal stories with insightful and emotionally powerful analysis. Moving from Bugs Bunny to Playboy Bunnies, Flashdance to Frozen, the progressive '70s through the backlash '80s, the glib '90s, and the pornified aughts–and at stops in between–she explains how growing up in the shadow of "the girl" taught her to think about herself and the world and what it means to raise a daughter in the face of these contorted reflections. In the tradition of Roxane Gay, Rebecca Solnit, and Susan Sontag, Chocano brilliantly shows that our identities are more fluid than we think, and certainly more complex than anything we see on any kind of screen."–Page 4 of cover.
Section: xxvi, 275 pages : illustration ; 21 cm
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; représentation des femme*; sofia; systèmes d'oppressions; thématiques

Identités et cultures: politiques des cultural studies - Hall, Stuart; Cervulle, Maxime; Jaquet, Christophe (Éditions Amsterdam, 2017)
À l'heure où se développent en France les premiers cursus d'études culturelles inspirés des cultural studies anglophones et où les politiques de l'identité et des représentations suscitent un intérêt croissant, la publication de ce recueil de quatorze essais classiques du sociologue britannique Stuart Hall constitue un détour nécessaire par les origines multiples et complexes de ce champ de réflexion. Intellectuel de renom international, Stuart Hall nous livre ici une généalogie critique des cultural studies, de leurs fondements théoriques marxistes et gramsciens à leur redéfinition des notions de "culture" et de "populaire", en passant par leur résistance aux disciplines classiques. Mettant en relief les préoccupations théoriques et politiques majeures des études culturelles, il interroge le concept d'" identité " et ses déclinaisons (ethnicité, race, classe, genre, sexualité) et développe une théorie qui situe la culture au cœur même du processus de construction identitaire. Qu'il analyse la formation des cultures diasporiques, les politiques noires britanniques, les situations postcoloniales ou le concept de " multiculturalisme ", Hall éclaire d'une lumière singulière nombre d'enjeux centraux de la scène politique internationale contemporaine.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; har4600; histoire et politique; intersectionnalité; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; études culturelles